Diatom assemblages from different substrates of the Casteldoria thermo-mineral spring (Northern Sardinia, Italy). Issue 1 (2nd January 2019) - Lai, Giuseppina G.; Padedda, Bachisio M.; Wetzel, Carlos E.; Cantonati, Marco; Sechi, Nicola; Lugliè, Antonella; Ector, Luc
Abstract: The thermo-mineral springs of Sardinia have historically been the object of several geochemical studies, whereas the biota and ecology have been totally neglected. The aim of this work is to contribute to the knowledge of the diatom microflora and ecology of the Casteldoria spring (northern Sardinia), in the hottest geothermal district of the Island. A total of 132 diatom taxa (56 genera) were found from three investigated substrates: rock (near the water emergence point), cobbles and sediments (in the spring-fed rivulet). Overall, 62 taxa (47% of the total) were common to other thermal springs of the Mediterranean area. Significant differences in the species composition among all substrates were highlighted by the ANOSIM test (global R = 0.554; p = 0.1%). The assemblages from rock formed a separated cluster from assemblages from cobbles and sediments in the nMDS plot. Rock-dwelling assemblages also had a lower species richness, probably due to the higher water temperature. Total suspended solids, discharge, water temperature and bromine were the most correlated environmental variables with diatom species and seem to influence both species composition and structure of assemblages. Some abundant taxa, such as Pinnularia joculata and Rhopalodia operculata, which fit well on high temperature and mineral content, can be considered representative taxa of the studied spring. This study underlines the importance of investigating different substrates to document diatom biodiversity in a more exhaustive way. It contributes to the knowledge of diatoms and ecology in thermo-mineral springs of Sardinia, providing first information on species composition at small-spatial and seasonal scale.